Understanding the factors controlling the hardness in martensitic steels. (1st January 2016) - Galindo-Nava, E.I.; Rivera-Díaz-del-Castillo, P.E.J.
Graphical abstract: Abstract: A unified description for the hardness in martensitic steels for a wide range of carbon contents is presented. It is based on describing the strength contributions of lath and plate martensite, precipitates and retained austenite. Descriptions of the dislocation density in both martensitic structures are obtained in terms of carbon content and tempering conditions. It is shown that a peak in hardness usually observed for carbon contents ranging 0.6–1 wt% is a result of a compromise between the strength of martensite, and the increase in retained austenite. A parametric analysis is performed suggesting possible scenarios for hardness improvement.